Karakteristik Asap Cair dari Kulit Buah Nipah (Nypa fruticans) dan Potensinya Sebagai Antibakteri Staphylococcus aureus - Mardiyana; Evila Purwanti Sri Rahayu, Theresia; Prasetya, Vicky (Cenderawasih University, 2023)
Skin of Nipah fruit (Nypa fruticans) contains cellulose, hemicellulose and lignin compounds, so it has the potential to be used as raw material for making liquid smoke. The urgency of this research is that until now the use of palm fruit skin to make liquid smoke is still very rare or non-existent. This research aims to characterize the contents of liquid smoke from Nipah fruit skin and determine its potential as an antibacterial against Staphylococcus aureus bacteria. The research stages were divided into 3 stages, namely the liquid smoke production stage, the liquid smoke characterization stage and its antibacterial potential, and the data processing stage. The data obtained was analyzed comparatively descriptively. The research results showed that the compounds contained in liquid smoke included total acids (as acetic acid), total phenolics and carbonyls. With the compounds contained and its acidic pH value, liquid smoke from Nipah fruit peel (Nypa fruticans) has very strong antibacterial capabilities at a concentration of 100%. Thus, this liquid smoke has the potential to be used as an antibacterial agent against Staphylococcus aureus bacteria